The tern creativity Reading in the light of cultural interpretation - يونس, وضحى (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research gives special attention to the term critical and is considered as a relationship of interaction. Change and creation. It is an intellectual. Cultural. Social and concept that has a close relationship with Arab culture as its original inspiration. The research will select a specific term which is creative. It will examine the linguistic forms that crystallize the creative term. The inventor. The generator and the creative. These concepts are revolving in its orbit. forming differentiated. Interdependent and compatible contexts without any controversy. The light of its narrow framework. Ie. Its lexical significance to be studied considering the relationship between diverse knowledge in its formation. The research will monitor the concept in the context of the most important monetary issues that intersected with it. Creativity is a phase of transition between two technical doctrines in Arabic literature .Vkrien are the say old and the updated mind finite to determine the cultural value of the term between being too and a way that is both together.